(untitled) (Bioagro, 2021)
Chrysophyllum cainito is a fruit tree native to Panama, but despite its nutritional and medicinal importance, there are few studies on its foliar anatomy. A collection of leaves was carried out in Cárdenas, Tabasco, Mexico, and in the laboratory, traditional histological techniques were applied to study the architecture and foliar anatomy. The venation pattern was identified and the thickness of the abaxial and adaxial epidermis, mesophyll, type and size of stomata, stomatal frequency, and trichomes were identified, as well as the tissues of the midrib. The foliar architecture of this species is similar in some characteristics to that of C. rufum and Manilkara spp. as the fact that they are brochidodromas and present intersecond and tertiary veins randomly arranged. The rectangular shape of the epidermal cells in this study was found to coincide with Nigerian C. cainito and C. rufum. Paracytic stomata are peculiar only in the analyzed C. cainito leaves and in the Thai species. The main rib of C. cainito is considered bicolateral in a closed arch analogous to C. cainito Thai. Likewise, in this work, coincidences with the species of the Sapotaceae family to which it belongs were identified, such as the presence of a unilayered epidermal layer, hypostomatic leaves, calcium oxalate crystals, and tector and “T” branched trichomes located on the abaxial surface. New attributes such as epidermis thickness, stomatal size, stomatal frequency, and midrib details were added.